Development of a tool for training the drag flick penalty corner in field hockey - Meulman, H. N.; Berger, M. A. M.; van der Zande, M. E.; Kok, P. M.; Ottevanger, E. J. C. (Procedia Engineering, 2012)
The drag flick technique in field hockey is an important `weapon` for scoring. Unfortunately, especially younger sportsmen often drop out when training the drag flick. A training tool was developed to improve the drag flick technique, to decrease the load on the body during the drag flick, and to increase the fun factor. A survey showed that trainers and hockey players were positive about the tool on all of the three aspects. Video analysis showed that training the drag flick with the tool reduced the load on the lower back. There was no difference in ground reaction force.